Correlations of Attitude to Avoid Sharing Risk and Trust with Informal Knowledge Sharing - Nugroho, Mahendra Adhi (International Journal of Economics, Business and Management Studies, 2012)
Knowledge sharing is one of sub issues in knowledge management. This research aims to investigate the relationship among informal knowledge sharing, attitude to avoid sharing risk and Trust. The data collected from 439 respondents. Statistical power analysis was run to reject type 1 and type 2 statistical errors and to get practical significations on hypotheses test results. Instrument validity of this research tested using discriminant validity and convergent validity. Instrument of this research has good reliability score. This research use first order Partial Least Square (PLS) technique to test research model. Attitude to Avoid Sharing Risk have negative correlation with Informal Knowledge Sharing. Attitude to Avoid Sharing Risk have negative correlation with Trust. Trust has a positive correlation with Informal Knowledge Sharing. This research does discussion using descriptive data and individual character of respondents. This research use extraversion and openness to experiences, two of basic individual characters, to explain unsupported hypotheses. Two interesting findings are identified first respondent concern on sharing risk is one of key factors in informal knowledge sharing behaviors. Second, individual characteristics will influence overall sharing behavior.